Carbon Dioxide Utilisation. Volume 2, - North, Michael; Styring, Peter (De Gruyter STEM, 2019)
The conversion of CO2 to chemicals and consumables is a pioneering approach to utilize undesired CO2 emissions and simultaneously create new products out of sustainable feedstock. Volume 2 describes several routes to transform CO2 into various compounds by catalytic and electrochemical as well as photo- and plasma induced reactions. Both volumes are also included in a set ISBN 978-3-11-066549-9.